2007
DOI: 10.1108/17473610710757491
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering retail shopping motives of Indian youth

Abstract: PurposeThe retail boom in India brings tremendous opportunities for foreign as well as domestic players. The changing lifestyle of the Indian consumer makes it imperative for the retailers to understand the patterns of consumption. The changing consumption patterns trigger changes in shopping styles of consumers and also the factors that drive people into stores. Hence, the key objective of this paper is to uncover the motives that drive young people to shop in departmental stores or malls.Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 18 publications
5
61
0
2
Order By: Relevance
“…19,20,90,99 Mall involvement for the current research suggests that age was an important predictor. Younger consumers may be more inclined to spend time in malls, as malls offer products, brands and entertainment facilities that match their lifestyle.…”
Section: Discussionmentioning
confidence: 61%
“…19,20,90,99 Mall involvement for the current research suggests that age was an important predictor. Younger consumers may be more inclined to spend time in malls, as malls offer products, brands and entertainment facilities that match their lifestyle.…”
Section: Discussionmentioning
confidence: 61%
“…Impulse purchases are likely encouraged in a pleasant shopping atmosphere (Crawford & Melewar, 2003;Kaur & Singh, 2007). Mattila and Wirtz (2008) observed over-stimulating in-store environment (pleasant music background, warm colors, fragrance, scents, etc.,) positively influences impulse buying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Park et al, (2006) found that impulsive buyers are consumers with hedonistic characteristics and diligently follow fashion trends; they gain pleasure and happiness from finding the products they want. Kaur & Singh (2007) found that teenagers, when they shopped, got a pleasurable and sensoric stimulation that influenced their impulse buying. Silvera et al, (2008) stated that impulsive buying was influenced by the consumers' positive emotions.…”
Section: Ruswanti 83mentioning
confidence: 99%